2015
DOI: 10.4034/pboci.2015.151.10
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Perception of Caregivers and Impact of Early Childhood Caries on Quality of Life Related to Oral Health of Preschool Children and their Families

Abstract: Objective: To identify risk factors, feeling of guilt, perception of caregivers and to evaluate the impact of early childhood caries (ECC) on quality of life related to oral health of children and their families. Material and Methods: 40 preschoolers were included in this study. Data were collected through an interview with caregivers regarding sociodemographic data, risks factors and ECC. Data on perception of caregivers related to child's oral health, as well of questionnaire to evaluate quality of life -BEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…These values are similar to those found in Recife (PE) (25% of children with dmft greater than or equal to 5) [18]. Dental caries early established in childhood interferes in the quality of life of children and their families [25].…”
Section: Discussionsupporting
confidence: 74%
“…These values are similar to those found in Recife (PE) (25% of children with dmft greater than or equal to 5) [18]. Dental caries early established in childhood interferes in the quality of life of children and their families [25].…”
Section: Discussionsupporting
confidence: 74%
“…The Brazilian Information System on Live Births is a reliable source of information for the analysis of live births with orofacial clefts (18,23). Therefore, considering the prevalence found and the negative impact that this condition implies on the quality of life of these children and family members (2,29,30), the care provided by the government to those born with orofacial clefts should be made in a comprehensive way through the adoption of public health policies directed to this population group. Another measure of extreme relevance includes the implantation of specialized centers of care and rehabilitation to individuals with orofacial clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries are associated not only with tooth brushing [7], socioeconomic factors [8], but also with different diseases for example MS [9]. A previous study with 51 MS patients (18-50 years) revealed that these patients suffered more common carious teeth than control and 85% MS patients had progressive paradontopathics [9].…”
Section: Introductionmentioning
confidence: 99%